The Peculiarities of Rendering Indicative Mood Tenses in Literary Translation (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the peculiarities of rendering indicative mood tense forms in literary translation. The study focuses on the functional and stylistic role of tense usage in fictional discourse and the challenges arising from systemic differences between source and target languages. Based on a qualitative comparative analysis of literary texts and their translations, the research identifies common translation strategies such as tense shifts, aspectual reinterpretation, and contextual adaptation. The findings demonstrate that the translation of indicative tenses is not a mechanical grammatical process but an interpretative activity guided by narrative coherence, stylistic adequacy, and communicative effect. The article emphasizes the importance of functional equivalence in preserving the temporal structure and aesthetic value of literary texts.